Violence against Women: Widowhood Practices and the Church. Towards the Construction of a New Culture of African Womanhood - Umoh, Dominic (Advances in Social Sciences Research Journal, 2018)
This study is an attempted overview of the African oppressive structure against women, with special reference to widowhood - all in the name of culture. We shall envisage the journey so far towards their liberation thanks to Christianity through inculturation. This paper therefore proposes an unrelenting upgrading of this liberation scheme in favour of the African female folks, aligning the scheme with the contemporary situation of women in the wider world. This proposed insertion of the African woman into the broader global picture would however caution African women against losing their identity in the process and thereby being isolated from their African roots. Our basic method in this study is critical, explorative and analytic.